2020
DOI: 10.1097/bpo.0000000000001600
|View full text |Cite
|
Sign up to set email alerts
|

Where Have All the Fractures Gone? The Epidemiology of Pediatric Fractures During the COVID-19 Pandemic

Abstract: Background: During the COVID-19 pandemic, public health measures to encourage social distancing have been implemented, including cancellation of school and organized sports. A resulting change in pediatric fracture epidemiology is expected. This study examines the impact of the COVID-19 pandemic on fracture incidence and characteristics. Methods: This is a retrospective cohort study comparing acute fractures presenting to a single level I pediatric trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
267
6
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(330 citation statements)
references
References 21 publications
45
267
6
12
Order By: Relevance
“…We postulate this to be due to implemented restrictions and recommendations in our society. With only 327 COVID-related deaths by mid-June in Finland compared to harder hit countries such as United States, Italy, France, and the United Kingdom (8), the overall reduction in pediatric trauma patients in our study (24%) was relatively lower as compared to United States, for example, where fracture reduction was 58% (7).…”
Section: Discussionmentioning
confidence: 65%
“…We postulate this to be due to implemented restrictions and recommendations in our society. With only 327 COVID-related deaths by mid-June in Finland compared to harder hit countries such as United States, Italy, France, and the United Kingdom (8), the overall reduction in pediatric trauma patients in our study (24%) was relatively lower as compared to United States, for example, where fracture reduction was 58% (7).…”
Section: Discussionmentioning
confidence: 65%
“…2 ). Four centers 6 , 20 , 29 , 38 reported the attendance figures for outpatient clinics for both pandemic-era and pre-pandemic time periods, with an overall decrease of 63% being observed (84174/123967, 0.37, CI: 0.24 to 0.51).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported the proportion of polytrauma cases seen in the ED for both pre-pandemic and pandemic periods, with a general trend favoring the increased incidence of polytrauma during the COVID-19 era. 6 , 28 , 36 Bram et al. reported that 14.2% of pre-pandemic and 19.3% of pandemic-era ED cases presented with polytrauma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in patterns of paediatric emergency department attendances [2,3], accessing of community care [2] and increased acuity at the time of attendance at hospital [2,4] have all been reported. The epidemiology of specific pathology has also changed, for example, patterns of fractures [5].…”
Section: Dear Editormentioning
confidence: 99%